Sensitization of Primary Afferent Nociceptors Induced by Intradermal Capsaicin Involves the Peripheral Release of Calcitonin Gene-Related Peptide Driven by Dorsal Root Reflexes - Li, Dingge (2008)
Neuropeptides released from axons of primary afferent nociceptive neurons are the key elements for the incidence of neurogenic inflammation and their release is associated with dorsal root reflexes (DRRs). However, whether the release is due to the triggering of DRRs and plays a role in inflammation-induced pain still remain to be determined. The present study assessed the role of calcitonin gene-related peptide (CGRP) in sensitization of primary afferent nociceptors induced by activation of transient receptor potential vanilloid-1 (TRPV(1)) following intradermal injection of capsaicin and determined if this release is due to activation of primary afferent neurons antidromically by triggering of DRRs. Under dorsal root intact conditions, primary afferent nociceptive fibers recorded in anesthetized rats could be sensitized by capsaicin injection, as shown by an increase in afferent responses and lowering of the response threshold to mechanical stimuli. After DRRs were removed by dorsal rhizotomy, the capsaicin-evoked sensitization was significantly reduced. In dorsal root intact rats, peripheral pretreatment with a CGRP receptor antagonist could dose-dependently reduce the capsaicin-induced sensitization. Peripheral post-treatment with CGRP could dose-dependently restore the capsaicin-induced sensitization under dorsal rhizotomized conditions. Capsaicin injection evoked increases in numbers of single and double labeled TRPV(1) and CGRP neurons in ipsilateral dorsal root ganglia (DRG). After dorsal rhizotomy, these evoked expressions were significantly inhibited. PERSPECTIVE: These data indicate that the DRR-mediated neurogenic inflammation enhances sensitization of primary afferent nociceptors induced by capsaicin injection. The underlying mechanism involves antidromic activation of DRG neurons via up-regulation of TRPV(1) receptors whereby CGRP is released peripherally.